Descry and Divulge Hitch by Using Hitch Entrapment-Bug Catcher - Vivek, J; Hema, B; Apoorva, J (International Journal of Engineering and Technology, 2018)
Based on the recent survey they used to track the bugsÂ  which are stored for further uses. The system is updated with new data by the technician. To overcome this situation hitch entrapment is proposed to make testing session productive and record the details to aid the development team for quick Resolution. This work is associated with developer, tester and admin. This tool allows the developer and tester to post the queries and screenshots of their program and Admin will monitor the whole process..Â